2022
DOI: 10.3389/fmicb.2021.806504
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor Lrp of Pantoea stewartii subsp. stewartii Controls Capsule Production, Motility, and Virulence Important for in planta Growth

Abstract: The bacterial phytopathogen Pantoea stewartii subsp. stewartii causes leaf blight and Stewart’s wilt disease in susceptible corn varieties. A previous RNA-Seq study examined P. stewartii gene expression patterns during late-stage infection in the xylem, and a Tn-Seq study using a P. stewartii mutant library revealed genes essential for colonization of the xylem. Based on these findings, strains with in-frame chromosomal deletions in the genes encoding seven transcription factors (NsrR, IscR, Nac, Lrp, DSJ_0012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In the plant pathogen Erwinia amylovora , Lrp is necessary to express virulence genes that control motility and synthesis of exopolysaccharides, a function that becomes apparent when BCAA levels are low [ 46 ]. Similarly, in the corn pathogen Pantoea stewartia , Lrp is necessary to induce disease symptoms in the plant, indicative of successful virulence expression [ 48 ]. The evidence contributed by Tomassetti et al [ 45 ], Schachterle and Sundin [ 46 ], and Bartholomew et al [ 48 ] suggest that leucine degradation, and more broadly, BCAAs degradation, plays a positive role in virulence induction by lowering intracellular levels of BCAAs and allowing Lrp to transcribe virulence genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the plant pathogen Erwinia amylovora , Lrp is necessary to express virulence genes that control motility and synthesis of exopolysaccharides, a function that becomes apparent when BCAA levels are low [ 46 ]. Similarly, in the corn pathogen Pantoea stewartia , Lrp is necessary to induce disease symptoms in the plant, indicative of successful virulence expression [ 48 ]. The evidence contributed by Tomassetti et al [ 45 ], Schachterle and Sundin [ 46 ], and Bartholomew et al [ 48 ] suggest that leucine degradation, and more broadly, BCAAs degradation, plays a positive role in virulence induction by lowering intracellular levels of BCAAs and allowing Lrp to transcribe virulence genes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the corn pathogen Pantoea stewartia , Lrp is necessary to induce disease symptoms in the plant, indicative of successful virulence expression [ 48 ]. The evidence contributed by Tomassetti et al [ 45 ], Schachterle and Sundin [ 46 ], and Bartholomew et al [ 48 ] suggest that leucine degradation, and more broadly, BCAAs degradation, plays a positive role in virulence induction by lowering intracellular levels of BCAAs and allowing Lrp to transcribe virulence genes. The molecular mechanisms by which BCAAs impact gene expression in Pst DC3000 remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The water flow is blocked and symptoms appear, ranging from chlorotic lesions on leaves that eventually become necrotic and delay growth to rapid wilting and death in more susceptible plants. Stewartan also facilitates the pathogen's movement through the vessels or intercellular spaces, which increases virulence [114,122,124,125].…”
Section: Phytopathogenic Bacteria That Colonize Xylem Vesselsmentioning
confidence: 99%
“…The control function of two transcription factors, Lrp and IscR, is important for P. stewartii. These two transcription factors affect the colonization process, growth in maize and their effect on host growth (Bartholomew et al, 2022). De Maayer et al (2011 reported that the pantoea genus also involves VgrG and Hcp proteins which indirectly involve the type IV secretion system.…”
Section: Introductionmentioning
confidence: 99%